2020
DOI: 10.3390/pathogens9020101
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Antimalarial Drug Resistance in Plasmodium vivax from Returned Travellers to NSW, Australia during 2008–2018

Abstract: To monitor drug resistance in Plasmodium vivax, a multidrug resistance 1 (Pvmdr1) gene and a putative transporter protein (Pvcrt-o) gene were used as molecular markers for chloroquine resistance. The biomarkers, the dihydrofolate reductase (Pvdhfr) gene and the dihydropteroate synthetase (Pvdhps) gene, were also used for the detection of resistance to sulphadoxine-pyrimethamine (SP); this drug is often accidentally used to treat P. vivax infections. Clinical blood samples (n = 120) were collected from patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 57 publications
(123 reference statements)
1
8
0
Order By: Relevance
“…Interestingly, the K10 insertion is rarely observed in Thailand, the border region between Thailand and Myanmar, and the border region between Thailand and Cambodia [ 44 , 52 ]. Other studies have reported no association between the K10 insertion and in vitro or ex vivo P. vivax CQ resistance [ 22 , 53 , 54 ]. Given the geographical genetic differences among parasite populations, the prevalence of the Pvcrt-o K10 insertion shows significant temporal and spatial heterogeneity [ 55 ] and the discrepancy may have resulted from differences in geography, population movement or sample size issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the K10 insertion is rarely observed in Thailand, the border region between Thailand and Myanmar, and the border region between Thailand and Cambodia [ 44 , 52 ]. Other studies have reported no association between the K10 insertion and in vitro or ex vivo P. vivax CQ resistance [ 22 , 53 , 54 ]. Given the geographical genetic differences among parasite populations, the prevalence of the Pvcrt-o K10 insertion shows significant temporal and spatial heterogeneity [ 55 ] and the discrepancy may have resulted from differences in geography, population movement or sample size issues.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence polymorphism is relatively limited in the Pvcrt-o locus but a lysine (AAG) insertion at amino acid position 10 (K10), which was initially discovered in Southeast Asian strains, has been suggested to be associated with CQ resistance [ 21 ]. Since then, this polymorphism has been observed in both Southeast Asian and South American parasites [ 17 , 22 , 23 ]. The Pvmdr1 gene encodes a transmembrane protein of the parasite’s digestive vacuole with 12 transmembrane domains and 1464 amino acids, and was characterized in 2005 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike pfcrt , and in contrast to pvmdr 1, very few SNPs (~10) in pvcrt have been reported, however, most occur at very low frequency ( Barnadas et al, 2008 ; Joy et al, 2018 ; Noisang et al, 2020 ). The most common PvCRT polymorphism is a lysine insertion at position 10 (K10) ( Barnadas et al, 2008 ; Joy et al, 2018 ; Noisang et al, 2020 ; Silva et al, 2018a ). The K10 insertion has been observed in both Southeast Asian and South American parasites ( Noisang et al, 2020 ; Silva et al, 2018b .…”
Section: Candidate P Vivax Drug Resistance Genesmentioning
confidence: 95%
“…The most common PvCRT polymorphism is a lysine insertion at position 10 (K10) ( Barnadas et al, 2008 ; Joy et al, 2018 ; Noisang et al, 2020 ; Silva et al, 2018a ). The K10 insertion has been observed in both Southeast Asian and South American parasites ( Noisang et al, 2020 ; Silva et al, 2018b . ; Zhao et al, 2020 ).…”
Section: Candidate P Vivax Drug Resistance Genesmentioning
confidence: 99%
“… 82 The cause of resistance in P. vivax remains elusive due to the nature of the parasite’s dormant phase in the liver, low parasitemia, and difficulty in distinguishing relapse, recrudescence, and reinfection. 83 …”
Section: Choosing An Antimalarial Agent For Chemoprophylaxismentioning
confidence: 99%